Web application to help students and tutors in engineering courses: a case study - André, Gonçalo (2020)
The present paper describes the development of an application in a Computer Engineering course using open source software tools. The main goal is the implementation of an educational system to improve the interface between students and teachers, as well as to serve as a mean of communication and events spreading related to computing to all members of the academic community where it is installed. In a first stage the system was built and implemented in one educational Institution but it is now improved based on the collaboration of teaching staff, of other Portuguese Engineering Department, allied to computer Engineering students skills and motivation. The architecture, main features, results and future work of the developed system are reported through the sections of this paper.